International Guidlines for museum object information: the CIDOC Information Categories - International Council of Museums - International Committee for Documentation (2005)
[Dt.:] Die International Guidelines for Museum Object Information - The CIDOC Information Categories beschreiben Informationskategorien, die bei der Entwicklung eines Dokumentationssystems für die Objekte einer Museumssammlung verwendet werden können. Die Richtlinien können von Museen, nationalen Dokumentationsorganisationen oder Systementwicklern als Basis für eine funktionierendes Museumsdokumentationssystem genutzt werden. Die Seite bietet Informationen zu Inhalt, Aufbau und Funktion der Richtlinien, sowie zu den Zielen der Museumsdokumentation im Allgemeinen. - [Engl.:] The International Guidelines for Museum Object Information - The CIDOC Information Categories describes standard information categories which may be used in developing a documentation system for the items of a museum s collection. The guidelines can be used by museums, national documentation organisations oder system developers as a basis for a functional museum documentation system. The page features information on contents, structures and function of the guidelines as well as on the aims of museum documentation in general.